PRESENTATION Nº39 Eng - Editor, El (Última Década, 2020)
This 39th issue of Revista Última Década marks the beginning of the collaboration and direction of the Research Ring on Social Sciences: Youths. Socioeconomic, Sociopolitical, and Sociocultural Transformations of Youths in Contemporary Chile, in relation to the journal’s international edition and indexing (www.proyectojuventudes.cl).